Penerapan Fuzzy Mamdani Dengan Particle Swarm Optimization (PSO) Pada Penilaian Kinerja Dosen (Studi Kasus STMIK Kaputama) - Marto Sihombing; Ediman Manik (UNIVERSITAS PELITA HARAPAN, 2019)
Abstract– The use of technology at this time is very developed along with the development of the times, so there are still many young people who need to get proper teaching. The lessons can be obtained from what parents have taught in the home environment and lecturers at the College. Regardless of the responsibilities of parents at home, we as young people are also obliged to study in school to college to achieve our goals. There are many bona fide universities and even the tuition fees vary, but universities that have expensive fees cannot be used as a benchmark that the university is competent, both from the teaching staff and academic regulations in the college. A competent university is a university that has competent teaching staff. In the Teaching and Learning Process at Higher Education, lecturers have an important role in the success of students in mastering the material given. STMIK Kaputama evaluates the performance of lecturers through 3 (three) variables, namely: Material Variables, Discipline Variables and Attitude Variables. With parameter values: Very Low (SR), Low (R), Enough (C), Good (B) and Very Good (SB), from the parameters the results of the Lecturer Performance Assessment will be known. Then it is necessary to build an application to assess the performance of lecturers using Fuzzy Mamdani with Particle Swarm Optimization (PSO), so that the assessment of Lecturer Performance can be assessed quickly. Keywords: Lecturer Performance, Fuzzy Mamdani, PSO